2023
DOI: 10.1017/erm.2023.15
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated phosphate metabolism in autism spectrum disorder: associations and insights for future research

Abstract: Studies of autism spectrum disorder (ASD) related to exposure to toxic levels of dietary phosphate are lacking. Phosphate toxicity from dysregulated phosphate metabolism can negatively impact almost every major organ system of the body, including the central nervous system. The present paper used a grounded theory-literature review method to synthesise associations of dysregulated phosphate metabolism with the aetiology of ASD. Cell signalling in autism has been linked to an altered balance between phosphoinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 144 publications
0
2
0
Order By: Relevance
“…Genetic and functional studies show that these enzymes are often dysregulated in ASD ( 93-96 ). Understanding the dysregulation of phosphoinositides may offer opportunities to manage ASD in an improved way ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and functional studies show that these enzymes are often dysregulated in ASD ( 93-96 ). Understanding the dysregulation of phosphoinositides may offer opportunities to manage ASD in an improved way ( 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…These pieces of evidence support ASD as a potential risk factor for CVD, which is consistent with our findings. Interestingly, a recent study has found that the mechanism of comorbidity between ASD and CVD may be related to dysregulated phosphate metabolism ( 60 ), which provides a new direction for future research.…”
Section: Discussionmentioning
confidence: 99%